Clinical characteristics of cognitive impairment in patients with Parkinson's disease and its related pattern in 18F‐FDG PET imaging. Issue 12 (12th July 2018) - Wu, Lei; Liu, Feng‐Tao; Ge, Jing‐Jie; Zhao, Jue; Tang, Yi‐Lin; Yu, Wen‐Bo; Yu, Huan; Anderson, Tim; Zuo, Chuan‐Tao; Chen, Ling; Wang, Jian
Abstract: This study aimed to characterize the clinical features and the related cerebral glucose metabolism pattern of cognitive impairments in Parkinson's disease (PD) with positron emission tomography (PET) imaging. We recruited 168 PD patients and 100 age‐matched healthy controls of similar education and gender distribution. All of those enrolled underwent clinical assessment including the unified Parkinson's disease rating scale motor score, Hoehn and Yahr scale, and comprehensive neuropsychological tests including domains of executive function, attention, memory, visuospatial function, and language. Demographics and the results of cognitive measures were compared between patients and healthy controls. Cognition status was classified as PD patients with dementia (PD‐D), PD patients with mild cognitive impairment (PD‐MCI), or PD patients with normal cognition (PD‐NC). In 53 PD patients who underwent 18 F‐fluorodeoxyglucose ( 18 F‐FDG) PET imaging, correlations between Z ‐score values of the different cognitive domains and cerebral 18 F‐FDG uptake were assessed using statistical parametric mapping (SPM8) corrected for age and motor severity. A total of 23.2% of PD patients were PD‐MCI and 8.9% were PD‐D. In the group of PD‐MCI, 96.3% showed multiple‐domain deficits, with executive function and attention impairment most predominantly involved. All the cognitive domain scores with the exception of language correlated with 18 F‐FDG metabolisms, primarily in posterior temporo‐parieto‐occipital association cortical areas. This study found that cognitive impairment in PD particularly encompasses frontal/executive deficits. Posterior cortical areas, containing multiple neurotransmitters and neural circuits, may play an important role in the pathogenesis of cognitive impairment in PD.